Thymus zygis and thymus pulegioides as a source of phenolic compounds - Pereira, Olívia R. (2015)
Thymus is an important genus in the West Mediterranean region, where many species are cultivated for confection of several dishes, including salads, soups, stews and sauces. Many Thymus, including T. zygis and T. pulegioides are also commonly used in traditional medicine. Whist phenolic compounds are commonly associated to health-beneficial properties of Thymus, the specific phenolic composition of T. zygis and T. pulegioides is presently unknown. The extracts of the aerial parts of T. zygis and T. pulegioides species were prepared with hot water as previously described. Total phenolic contents were determined according to the adapted Folin-Ciocalteu colorimetric method and the identification of the phenolic compounds was performed by high performance liquid chromatography (HPLC-DAD). The extracts of T. zygis and T. pulegioides contained 319±44 and 391±3 μg GAE/mg, respectively. Likewise other Thymus species, both extracts were enriched in caffeic acid derivatives, showing characteristic UV spectra maxima at 290 and 328 nm. The two extracts also contained moderate amounts of the flavone luteolin-7-O-glucoside that has been previously described in others Thymus species. Yet, T. zygis and T. pulegioides phenolic profiles could be clearly distinguished: while the first had high levels of the phenolic acid salvianolic acid K the extract of T. pulegioides was enriched in eriodictyol derivatives. The phenolic compounds of T. zygis and T. pulegioides are here described for the first time.